2017
DOI: 10.1038/cr.2017.90
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the B7-H3 immune checkpoint limits tumor growth by enhancing cytotoxic lymphocyte function

Abstract: The interaction between tumor and the immune system is still poorly understood. Significant clinical responses have been achieved in cancer patients treated with antibodies against the CTLA4 and PD-1/PD-L1 checkpoints; however, only a small portion of patients responded to the therapies, indicating a need to explore additional co-inhibitory molecules for cancer treatment. B7-H3, a member of the B7 superfamily, was previously shown by us to inhibit T-cell activation and autoimmunity. In this study, we have anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
216
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(224 citation statements)
references
References 32 publications
8
216
0
Order By: Relevance
“…We also noticed that B7‐H3 expression was negatively associated with NK cell‐related immune response, consistent with the results reported by Lee et al. (2012) …”
Section: Resultssupporting
confidence: 92%
“…We also noticed that B7‐H3 expression was negatively associated with NK cell‐related immune response, consistent with the results reported by Lee et al. (2012) …”
Section: Resultssupporting
confidence: 92%
“…Preclinical studies suggested that combining PD-1 blockade with costimulatory agonists, immune checkpoint blockade (such as blockade of CTLA-4, 116 B7-H3, 53,117 CD270, 53 CD200R, 53,100 LAG-3, 60 or TIM-3 50,52,118 ), or other therapeutic agents (such as lenalidomide 53 Some combination trials have interim results available. Nivolumab and ipilimumab combination therapy had ORRs of 74% in HL and 20% in B-NHL in a phase 1 trial.…”
Section: Pd-l1 Expression and Clinical Roles In B-cell Lymphomasmentioning
confidence: 99%
“…Using both the CCLE and pan-cancer TCGA datasets, the expression of each of these genes was assessed in relation to our stemness signature (Figures 6C and 6D). This revealed positive associations between stemness and a number of immunoinhibitory genes, including CD276 (B7-H3, shown to inhibit T cell activation and autoimmunity (Lee et al, 2017), PVR (CD155, a member of the B7/CD28 superfamily, shown to exhibit potent inhibitory action in different subsets of immune cells (Mahnke and Enk, 2016), and TGFB1 (a key player in the induction of immunological tolerance (Johnston et al, 2016). Thus, the stemness phenotype involves the expression of several gene products that could potentially serve as targets for immune modulation.…”
Section: Tumor Cell Intrinsic Mechanisms Of Stemness-mediated Immunosmentioning
confidence: 99%